Metabolic functions of the tumor suppressor p53: Implications in normal physiology, metabolic disorders, and cancer - Matthieu Lacroix; Romain Riscal; Giuseppe Arena; Laetitia Karine Linares; Laurent Le Cam (Elsevier, 2020)
Background: The TP53 gene is one of the most commonly inactivated tumor suppressors in human cancers. p53 functions during cancer progression have been linked to a variety of transcriptional and non-transcriptional activities that lead to the tight control of cell proliferation, senescence, DNA repair, and cell death. However, converging evidence indicates that p53 also plays a major role in metabolism in both normal and cancer cells. Scope of review: We provide an overview of the current knowledge on the metabolic activities of wild type (WT) p53 and highlight some of the mechanisms by which p53 contributes to whole body energy homeostasis. We will also pinpoint some evidences suggesting that deregulation of p53-associated metabolic activities leads to human pathologies beyond cancer, including obesity, diabetes, liver, and cardiovascular diseases. Major conclusions: p53 is activated when cells are metabolically challenged but the origin, duration, and intensity of these stresses will dictate the outcome of the p53 response. p53 plays pivotal roles both upstream and downstream of several key metabolic regulators and is involved in multiple feedback-loops that ensure proper cellular homeostasis. The physiological roles of p53 in metabolism involve complex mechanisms of regulation implicating both cell autonomous effects as well as autocrine loops. However, the mechanisms by which p53 coordinates metabolism at the organismal level remain poorly understood. Perturbations of p53-regulated metabolic activities contribute to various metabolic disorders and are pivotal during cancer progression. Keywords: p53, Metabolism, Normal tissue homeostasis, Cancer